Temperature Rise Characteristic of Circuit Breakers Based on New Environmentally Friendly Gas - Lihua ZHAO; Zhiyun WU; Zhiqiang YAN; Xiaolong HUANG; Wenjun NING; Shenli JIA (工程科学与技术)
Objective Due to the significant greenhouse effect of SF6 circuit breakers, research on circuit breakers using new environmentally friendly gases has garnered considerable attention. Existing studies on the C4F7N/CO2 gas mixture primarily focus on arc extinguishing and insulation performance, yet investigations into its temperature rise characteristics remain insufficient. However, these characteristics are crucial for designing the current-carrying capacity and monitoring the operational condition of the circuit breaker. Therefore, this study investigates the temperature rise characteristics of environmentally friendly gas circuit breakers based on a 40.5 kV porcelain column circuit breaker prototype.Methods The internal structure of the interrupter chamber in the porcelain column circuit breaker is disassembled to analyze the current path and the mechanisms of heat generation and transfer. The thermal process primarily occurs inside the interrupter chamber, with the primary heat sources being the conductor circuit and the contact points between the movable and static contacts. Based on this, a temperature rise experimental platform is constructed. The arrangement of temperature sensors and the testing scheme are established, providing a data foundation for further studies on temperature rise characteristics. This research develops a simulation model of electromagnetic-thermal-fluid multi-physical field coupling based on the experimental prototype at a 1∶1 scale to explore the temperature rise mechanism. It employs the finite element method to calculate the temperature rise and fluid field distribution inside the interrupter chamber. The simulation’s material parameters and boundary conditions are consistent with those in the experiment.Results and Discussions The experimental and simulation temperature rise curves are closely aligned, with the temperature rise error at designated measurement points, such as the primary contact, arc contact, and nozzle, not exceeding 10%. Thus, the experiment validates the simulation model. This simulation provides a method for studying the overall temperature rise and flow field distribution of the circuit breaker, addressing the limitation of experimental measurements to only certain parts of the circuit breaker. By integrating experiments and simulations, this study also identifies the significant heating at the contact surface between the primary and arc contacts due to high current and power density. This is attributable to the small cross-section of the load current and high film resistance at the contact surface. This study indicates the temperature rise characteristics and flow field distribution of the new environmentally friendly gas circuit breaker using two analytical methods: experimental testing and simulation calculation. It also analyzes the temperature rise field and flow field distribution characteristics of the 40.5 kV porcelain column circuit breaker regarding current magnitude, insulating gas type, and gas mixture components.Conclusions The results showed that the temperature rise within the circuit breaker interrupter is symmetrical, exhibiting a step-like distribution with higher temperatures at the top and lower temperatures at the bottom. The heat is primarily concentrated in the conductor and the top of the internal insulating gas. The flow field distribution inside the interrupter remains relatively stable, with the gas near the conductor experiencing natural convection due to heat. The gas flow rate increases with the temperature, reaching its maximum at the nozzle. Under certain conditions, the temperature rise in the conductor circuit of the porcelain column circuit breaker, the porcelain casing shell, the nozzle, and other typical measurement points increases with the rise in load current. The temperature rise rate at the nozzle and conductor is significantly higher than at the porcelain casing shell. The temperature rise field of the porcelain column circuit breaker, when utilizing different gases, follows a similar distribution law. The C4F7N/CO2 gas mixture shows good heat dissipation properties. As the proportion of C4F7N gas in the mixture increases, the temperature rise of the conductor gradually decreases. The flow field distribution inside the interrupter chamber is also similar across various gas environments. The gas flow velocity is closely related to the interrupter’s temperature and the gas’s viscosity. The results of this study provide a theoretical basis for applying the new environmentally friendly gas C4F7N in porcelain column circuit breakers. This is of great significance for replacing SF6 with new environmentally friendly insulating gases in managing the temperature rise of high-voltage circuit breakers.